Small-signal dynamic modeling of HVDC systems. - Osauskas, C. (IEEE Transactions on power delivery)
This paper details the development of a linear continuous-time state model of the small-signal dynamics of a high-voltage direct current (HVDC) transmission system. The dynamics in the frequency range between 2 and 200 Hz on the DC side are of interest for the identification of possible stability problems and the design of the fastest level of converter controls. The state model is formed by representing the system as the collection of a number of interconnected subsystems. This approach is structured and flexible, and can be directly applied to other systems including FACTS. A small-signal state model of the CIGRE benchmark HVDC transmission system is formed, validated against PSCAD/EMTDC time-domain simulation, and used to determine the rectifier DC current control open-loop frequency response.